Analisis Rasio Keuangan dalam Menilai Kinerja Keuangan PT. Diamond Food Indonesia Tbk yang Terdaftar di BEI Periode 2019- 2023 - Kurniati, Kurniati; Firayanti, Yuni; Mahardhika, Tubagus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the financial performance of PT. Diamond Food Indonesia Tbk, which is listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023, using financial ratio analysis that includes liquidity ratios, solvency ratios, activity ratios, profitability ratios, and market ratios. This research employs a descriptive qualitative approach with secondary data obtained from the company’s annual financial statements. The results of the study show that the company’s liquidity ratios, measured by the Current Ratio and Quick Ratio, remain below the industry standard, indicating that the company's ability to meet its short-term obligations is still inadequate. The solvency ratios, measured by the Debt to Asset Ratio and Debt to Equity Ratio, indicate that the company’s capital structure is relatively healthy with low financial risk. However, activity ratios such as Asset Turnover Ratio and Inventory Turnover Ratio still demonstrate low efficiency in utilizing assets to generate sales. The profitability ratios, measured by Return on Assets, Return on Equity, and Net Profit Margin, show that the company's ability to generate profits is still far from the industry standard, although there have been improvements in certain years. The market ratio, measured by Earnings Per Share (EPS), also shows fluctuations but has not yet displayed stable performance.